Optimal Feeding Frequency on the Growth Performance of Whiteleg Shrimp (Litopenaeus vannamei) during Grow-out Phase - Alif Ihsanario; Ahmad Ridwan (3BIO: Journal of Biological Science, Technology and Management, 2021)
Whiteleg shrimp (Litopenaeus vannamei) is a fisheries commodity that has experienced a vast increase in production since the early 1970s. As one of the largest contributors to the global shrimp market, Indonesia always tried to increase its shrimp production. To fulfill the global market demand, whiteleg shrimp farmers have met with countless obstacles, e.g., sub-optimal growth problem. Optimal feed management is one of the determining factors that account for the growth and production efficiency of whiteleg shrimp. Feed management practices include feeding frequency, methods of feed monitoring, and controlling. This literature review aims to provide an insight into the optimal feeding frequency for the growth, survival, and feed efficiency of whiteleg shrimp production. The method used for this review was a narrative review approach following the PRISMA scheme for literature sorting, which includes identification, screening, eligibility test, and inclusion. There were eight primary literatures from journals with H indices of 18, 50, 55, 72, 80, and 164 (four articles from Q1 journals and three from Q2 journals) and one article without index. Data analysis revealed that the growth rate was significantly affected by the feeding frequency of on-demand feeding system (AQ1) (P < 0.05), although no significant difference was found in regards to the survival rate and the FCR (P > 0.05). The optimal feeding frequency for industrial-scale shrimp production was found in the on-demand feeding system (AQ1).